Literature Review: The Role Of Big Data In Business Intelligence (BI) - Surya Jaya, Anton; Ari Pradhanawati; Andi Wijayanto (Cita konsultindo, 2025)
This literature review explores the pivotal role of Big Data in enhancing Business Intelligence (BI) capabilities, particularly in strategic decision-making, operational efficiency, and gaining a competitive advantage. Through an analysis of recent studies, it highlights how Big Data facilitates real-time insights, enabling firms to optimize processes, improve predictive analytics, and adapt to dynamic market conditions. The review integrates theoretical frameworks such as Dynamic Capability Theory and Resource-Based Theory to underline the strategic value of Big Data in BI. Despite its transformative potential, challenges like high implementation costs, technological complexity, and resource limitations hinder its adoption, particularly for small and medium-sized enterprises. This study identifies gaps in current research and calls for further exploration into cost-effective solutions and skill development to enable broader adoption across various industries and regions.